Serum antigliadin antibodies in cerebellar ataxias: a systematic review and meta-analysis. Issue 11 (4th June 2018) - Lin, Chi-Ying; Wang, Min-Jung; Tse, Winona; Pinotti, Rachel; Alaedini, Armin; Green, Peter H R; Kuo, Sheng-Han
Abstract : Background: Gluten sensitivity refers to prominent immunological responses to gluten, usually in conjunction with elevated levels of serum antigliadin antibody (AGA). The association between AGA and cerebellar ataxias has been inconsistently reported. Methods: We performed a systematic literature search and a meta-analysis to study the weighted pooled OR of idiopathic cerebellar ataxia (IDCA) cases to controls or to hereditary ataxia (HA) for AGA seropositivity using fixed effect model. Results: Eleven studies were included, with a total of 847 IDCA cases, 1654 controls and 445 HA cases. IDCA cases had fourfold higher odds than controls (OR 4.28, 95% CI 3.10 to 5.90) and twofold higher odds than HA cases (OR 2.23, 95% CI 1.45 to 3.44) of having AGA seropositivity. Sensitivity analysis excluding the most weighted study, which accounted for 69% of the total weight, still showed similar associations (IDCA vs controls, OR 3.18, 95% CI 1.79 to 5.67 and IDCA vs HA, OR 1.72, 95% CI 1.03 to 2.86, respectively). The subgroup analysis showed that, when compared with controls, IDCA cases of both East Asian and Western countries had approximately threefold to fourfold higher odds to have AGA seropositivity (OR 3.41, 95% CI 1.67 to 6.97 and OR 4.53, 95% CI 3.16 to 6.49, respectively), suggesting the lack of ethnic heterogeneity. The odds of AGA seropositivity for HA cases was not significantly higher than controls (OR 1.41, 95% CI 0.82 to 2.44). Conclusion: Our study indicates the association between AGA and IDCA, across different geographic regions.